RISK FACTORS AND PREVENTIVE INTERVENTIONS FOR PRESSURE INJURIES IN CANCER PATIENTS (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: identify and describe the risk factors for the development of pressure injuries in adult cancer patients and interdisciplinary preventive interventions. Method: integrative literature review. Data collection was carried out between March and April 2019 and December 2020, using the databases: BDENF; PubMed/Medline; Embase; Scopus; Cinahal and Web of Science. Results: the sample consisted of 16 articles published from 2008 to 2019. Among the risk factors identified, the following stand out: nutritional status, advanced age, incontinence and immobility; the interdisciplinary preventive interventions identified were: decubitus change, nutritional assessment and monitoring, skin care and use of support surfaces. Conclusion: further studies are needed to take a careful and assertive look at cancer patients.